2019
DOI: 10.1017/s0021859619000832
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urine nitrogen application rate on nitrogen transformations in grassland soils

Abstract: Urine is a critical nitrogen (N) input in temperate grazed grasslands and can drive substantial nitrous oxide (N2O) production in soils. However, it remains unclear how differences in the N input rate affect N2O fluxes and vary between different grassland soils. The effect of increasing urine N application on ammonium (NH4+), nitrite (NO2−) and nitrate (NO3−) concentrations and N2O production was tested in two grassland soils, a free-draining loam and an imperfectly drained sandy-loam. It was hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
5
5
1
Order By: Relevance
“…This finding was consistent with the research result of Huang et al on the Huang-Huai-Hai Plain [52]. However, C. Somerset al argued that nitrate-nitrogen accumulated significantly when the urea concentration was 300 kg•ha −1 , while ammonianitrogen accumulated most significantly when the urea concentration was 1000 kg•ha −1 [63]. This result may be due to the inhibition of NO 3 − formation by high concentration urea, which led to the accumulation of NO 2 − , followed by an increase in NH 4 + caused by NO 2 − denitrification [64].…”
Section: Effects Of Nitrogen Application On Soil Nutrientssupporting
confidence: 91%
“…This finding was consistent with the research result of Huang et al on the Huang-Huai-Hai Plain [52]. However, C. Somerset al argued that nitrate-nitrogen accumulated significantly when the urea concentration was 300 kg•ha −1 , while ammonianitrogen accumulated most significantly when the urea concentration was 1000 kg•ha −1 [63]. This result may be due to the inhibition of NO 3 − formation by high concentration urea, which led to the accumulation of NO 2 − , followed by an increase in NH 4 + caused by NO 2 − denitrification [64].…”
Section: Effects Of Nitrogen Application On Soil Nutrientssupporting
confidence: 91%
“…Similar to other studies carried out with bovine urine [22,33,34], our study showed higher pH levels from the beginning of the incubation period that followed the same trend as the N rate applied, with a similar trend in NH4 + concentrations and both variables declining over time. Accumulated NH4 + was reported to nitrify to NO2 − and NO3 − , generally within a few weeks after urine application to the soil [35], with longer periods also having been reported [36,37].…”
Section: N Rate and N Mineralizationsupporting
confidence: 90%
“…The oxidation of NH 3 has been identified as a limiting step in nitrification [18], which occurs through two steps of mutualistic symbiosis between ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) [19]. Several studies have shown that urinary N rates equivalent to 1000 kg N ha −1 inhibit nitrification, and this inhibition can be explained by the accumulation of NH 3 [14, [20][21][22]. However, the duration of this inhibition is variable [23].…”
Section: Introductionmentioning
confidence: 99%
“…Soil mineralization was studied over a period of 30 days in the current study. However, it should be noted that N transformations beyond the time examined (30 days) have also been reported (Somers et al, 2019); hence, the possibility to extend the incubation time should be considered in follow-up experiments. It would have been beneficial to measure soil urea concentration directly, although, for these two soils, the loss of urea was probably well reflected in the increase of mineral N through the early part of the incubation.…”
Section: Discussionmentioning
confidence: 98%